The Bethesda System terminology for cervical cytology reports brought up to date - Albújar, Pedro (2015)
The Bethesda System was first proposed at a workshop sponsored by the National Cancer Institute of the United States, held in the city of Bethesda, in December 1988. The meeting, attended by a host of cytopathologists, was motivated the need to standardize terminology and standardize the characteristics of the reporting of the results. He recognized the cytological report as a formal medical consultation and is cytopathologists ultimately, medical and legal responsibility of the cytological diagnosis.